SPE Annual Technical Conference and Exhibition 1983
DOI: 10.2118/12109-ms
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Effects of Hydraulic Stimulation by Microseismic Event Location: A Case Study

Abstract: One of the most prom1 S1 ng techni ques for monitoring the effects of hydraulic stimulation or fracturing is the use of the induced microseismicity to defi ne the shape and ori entati on of the sti mul ated regi ons. The results presented in thi s paper are believed to be the first of their kind with an on-line location system mapping the stimulated zone during injection. The stimulation was undertaken as part of an investigation into the generation of hot dry rock geothermal reservoirs and consisted of a 3.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…Initially, the technology was developed for geothermal energy business (Albright and Pearson, 1982;Batchelor, Baria and Hearn, 1983), but found its way in stimulation monitoring application for unconventional reservoirs, including shale gas and tight oil reservoirs.…”
Section: Microseismic Monitoringmentioning
confidence: 99%
“…Initially, the technology was developed for geothermal energy business (Albright and Pearson, 1982;Batchelor, Baria and Hearn, 1983), but found its way in stimulation monitoring application for unconventional reservoirs, including shale gas and tight oil reservoirs.…”
Section: Microseismic Monitoringmentioning
confidence: 99%
“…Pearson (1981) and Phillips et al (1997) analyzed microseismicity generated during the stimulation of the 2930 m deep "large Phase 1" and the 3460 m deep Phase 2 reservoirs, respectively, at the Fenton Hill EGS site, New Mexico. Batchelor et al (1983) summarize microseismicity observed during the stimulation injections into the Phase 2a and 2b reservoirs at Rosemanowes in Cornwall, UK. Tezuka and Niitsuma (2000) examined clusters of microseismic events generated during the stimulation of the 2200 m deep reservoir at the Hijiori EGS site in Japan.…”
Section: Induced Seismicitymentioning
confidence: 99%
“…However, the possibility of predicting not only impending failure, but also the location of the unstable zone within the landslide, must result eventually in its more widespread use. Certainly, the instrumentation and analytical methods developed for the location of fractures propagating through the rock mass following hydraulic fracturing described by Batchelor et al (1983) can be directly applied to landslides. The manpower requirements can be considerably reduced by using the automatic triggering system for recording events developed by Houliston et al (1982) and this does mean that continuous on-line monitoring can be achieved.…”
Section: Microseismic Monitoringmentioning
confidence: 99%